The relative abundances of resolved l2CH2D2 and 13CH3D and mechanisms controlling isotopic bond ordering in abiotic and biotic methane gases. (15th April 2017) - Young, E.D.; Kohl, I.E.; Lollar, B. Sherwood; Etiope, G.; Rumble, D.; Li (李姝宁), S.; Haghnegahdar, M.A.; Schauble, E.A.; McCain, K.A.; Foustoukos, D.I.; Sutclife, C.; Warr, O.; et al.
Abstract: We report measurements of resolved 12 CH2 D2 and 13 CH3 D at natural abundances in a variety of methane gases produced naturally and in the laboratory. The ability to resolve 12 CH2 D2 from 13 CH3 D provides unprecedented insights into the origin and evolution of CH4 . The results identify conditions under which either isotopic bond order disequilibrium or equilibrium are expected. Where equilibrium obtains, concordant Δ 12 CH2 D2 and Δ 13 CH3 D temperatures can be used reliably for thermometry. We find that concordant temperatures do not always match previous hypotheses based on indirect estimates of temperature of formation nor temperatures derived from CH4 /H2 D/H exchange, underscoring the importance of reliable thermometry based on the CH4 molecules themselves. Where Δ 12 CH2 D2 and Δ 13 CH3 D values are inconsistent with thermodynamic equilibrium, temperatures of formation derived from these species are spurious. In such situations, while formation temperatures are unavailable, disequilibrium isotopologue ratios nonetheless provide novel information about the formation mechanism of the gas and the presence or absence of multiple sources or sinks. In particular, disequilibrium isotopologue ratios may provide the means for differentiating between methane produced by abiotic synthesis vs. biological processes. Deficits in 12 CH2 D2 compared with equilibrium values in CH4 gas made by surface-catalyzed abiotic reactions are so large as to point towards a quantum tunneling origin. Tunneling also accounts for the more moderate depletions in 13 CH3 D that accompany the low 12 CH2 D2 abundances produced by abiotic reactions. The tunneling signature may prove to be an important tracer of abiotic methane formation, especially where it is preserved by dissolution of gas in cool hydrothermal systems (e.g., Mars). Isotopologue signatures of abiotic methane production can be erased by infiltration of microbial communities, and Δ 12 CH2 D2 values are a key tracer of microbial recycling.